Comparison of Surgical Success for Infantile Esotropia and Strabismus Associated with Neurological Impairment. (2nd July 2016) - Kiziltunc, Pinar Bingol; Atilla, Huban; Çalış, Feyza; Alay, Cem
ABSTRACT: Purpose : Surgery for strabismus associated with neurological impairment is assumed to have unsatisfactory results in comparison with other strabismus cases. The aim of this study is to compare the surgical success rates of infantile esotropia (IE) and strabismus associated with neurological impairment. Methods : The records of 103 patients that received operations for IE and strabismus associated with neurological impairment between January 1994 and May 2014 were reviewed retrospectively. The angles of deviation and surgical success rates were evaluated at preoperative, 1-month postoperative, and 24-month postoperative visits. Results : Forty-five patients received operations for strabismus associated with neurological impairment (25 patients with esotropia and 20 patients with exotropia) and 58 patients for IE. Mean preoperative angles of deviation in cases with neurological impairment were 42 prism diopters (PD) for esotropia, 44.7 PD for exotropia, and 44.4 PD for IE. One patient from each group had consecutive deviation at first visit, and at last visit, 3 patients with neurological impairment and 5 patients with IE had consecutive deviations. Surgical success rates at the end of the second year were 52% for esotropia and 50% for exotropia in patients with neurological impairment and 56.8% for IE cases. Conclusion : This study was unable to find the differences between surgical success rates in IE and strabismus associated with neurological impairment.